Association of serum metallic ion levels in patients with total joint arthroplasty with their adverse effects: a comparative cross-sectional study - Rehan, Harmeet Singh; Singh, Jasbir; Arora, Tarun; Kalra, Mukesh; Gupta, Lalit Kumar; Das, Mukul; Singh, Rakhi (International Journal of Research in Orthopaedics, 2025)
Background: Metallic implants used in joint arthroplasty release ions gradually sometimes resulting in their toxicity. Hence, data regarding exact correlation between serum metallic ion levels and toxicity occurrence is still lacking. Methods: A total of 90 adult subjects, each with a single total joint arthroplasty (TJA between 1 to 5 years), or without were recruited. The serum levels of Cr, Co, Ni, & Mo in above 2 groups were estimated and correlated with signs and symptoms related to Cr, Co, Ni, & Mo ion toxicity Unpaired Student's t-test, Chi-square test and Pearson correlation coefficient were used to analyses data. A p value<0.05 was considered significant. Results: The mean serum levels of Cr (21.53±7448 µg/l vs. 19.03±0.3372 µg/l; p=0.0026), Ni (9.643±0.2486 µg/l vs. 9.303±0.2729 µg/l; p=0.83), Co (5.482±0.20 µg/l vs. 5.573±0.21 µg/l; p=0.76), and Mo (5.573±0.2159 µg/l vs. 5.290±0.2208 µg/l; p=0.36) in subjects with implants were higher than in subjects without implants. Five subjects reported six adverse effects (AE) specifically numbness in hands (4), fatigue (1), and bone pain (1), which showed no significant association or correlation with the mean serum levels of the metallic ions. Conclusion: Results showed increased mean serum chromium levels post one year of implant surgery, while mean serum levels of Co, Ni, and Mo did not demonstrate any significant elevation. No correlation between serum levels of Cr, Co, Ni, and Mo, duration of implant, and observed AE was seen. Causality assessment between reported AE and metal ions (Cr, Co, Ni, and Mo) levels was “possible."